The effectiveness of grammatical mental imagery with cognitive processing on self-efficacy, emotional processing and spirituality in mothers of students with autism spectrum disorder. - Safikhani, Faride (International Journal of Education and Cognitive Sciences, 2022)
The aim of this study was to determine the effectiveness of grammatical mental imagery with cognitive processing on self-efficacy, emotional processing and spirituality in mothers of students with autism spectrum disorder in terms of practical purpose and cross-sectional data collection method and quasi-experimental pre-test-post-test research method with control group. The statistical population of all mothers of students with autism spectrum disorder in two schools under the supervision of education in Ahvaz was 105 students in 1398. A total of 30 mothers with children with autism spectrum disorder were randomly selected and 15 people were randomly assigned to the group of grammatical mental imagery with cognitive processing and 15 people were in the control group. The research instruments were the Long Form Nefar Self-Compassion Questionnaire (2003), Hall and Edwards (1986) Spirituality Scale, Scanning et al. (2010) and the grammatical mental imagery protocol with cognitive processing by Smoker (1995). The collected data were performed by descriptive and inferential statistical methods of analysis of covariance and by SPSS software version 24. The results showed that the simultaneous effect of group type and test status (pre-test and post-test) on self-efficacy scores p = 0.00, F = 62.208), emotion processing (p = 0.00, F = 107.237) and spirituality p = 0.00, 407/36 was F =). These findings indicate the effect of treatment on the desired variables. Therefore, we conclude that grammatical mental imagery with cognitive processing has a positive effect on self-efficacy, emotional processing and spirituality of mothers with children with autism spectrum disorder.